Internalization of the Pesisiran Javanese Cultural Values through Fine Art Education at One Roof State Primary-Secondary Schools in Wedung Village, Demak Regency - Setyobudi, Setyobudi; Florentinus, Totok Sumaryanto; Triyanto, Triyanto (The Journal of Educational Development, 2018)
As a social institution of education, the school has a mission to instill cultural values in the students’ mind. The problems of this research are (1) how is the characteristic of coastal Javanese cultural values at the village of Tambak Seklenting, Sub-district of Wedung, Demak Regency? (2) Why do the values of coastal Javanese culture need to be internalized to the students? (3) What is the form of art in the elementary-junior high school? This research was designed as a case study using a qualitative approach. The focus and targets of this research are (1) characteristics of coastal Javanese cultural values, (2) the importance of the coastal Javanese cultural values to be internalized to the students in the elementary-junior high school, (3) the artwork in the elementary-junior high schools. The data were drawn using observation techniques, interviews, and documentation studies. The research data were analyzed using interactive analysis models consisting of reduction, presentation, and data verification stages. The results of this study are as follows. First, the characteristics of coastal Javanese culture are oriented towards the Islamic religious values and the Javanese culture. Second, the values of coastal Javanese culture are important to be internalized to students for character building. Third, the process of internalization of Javanese coastal cultural values is done through art education which includes objectives, materials, methods, activities, results, and assessment of learning outcomes. Fourth, the students’ artworks of the One Roof State Primary-Secondary Schools in Wedung are influenced by the coastal environment and Islam.